Mapping of Flood-Prone Areas in Malaka Regency Based on WebGIS Using the Simple Additive Weighting (SAW) Method - Dety Lestari, Anastasia Kadek; Bria, Adriana Laurensia (Journal of Information and Technology, 2025)
Malaka Regency in East Nusa Tenggara Province is a flood-prone area, mainly due to high rainfall and the overflow of the Benenain River, the largest watershed in the province. This study aims to map flood-prone areas using the Simple Additive Weighting (SAW) method integrated into a WebGIS-based decision support system. The variables considered include rainfall, land use, slope, topography, and river flow. The analysis resulted in three flood vulnerability classifications: low (Laenmanen, Iokafeu, Botinleobele, Sasitamean), moderate (Kobalima, Kobalima Timur, Malaka Timur, Rinhat), and high (Malaka Tengah, Malaka Barat, Weliman, Wewiku). This system is expected to assist local governments in making timely and accurate decisions for flood disaster management and mitigation